Health promotion and quality of life in a period of social isolation using therapeutic gymnastics in a virtual environment (Research, Society and Development, 2022)
Social isolation to contain the pandemic of COVID-19 may contribute to increase sedentarism, requiring strategies such as the use of virtual media to increase the practice of physical activity. The objective of this study was to evaluate the effects of Lian Gong therapeutic gymnastics, in a virtual environment, on health promotion and quality of life. Participated 19 volunteers with a mean age of 53.4 years (22 to 78), 18 were female and one male. They were submitted to an assessment of quality of life through the SF-36 questionnaire, applied online, before and after the intervention, and they answered questions for qualitative assessment about their participation after the intervention. The intervention with the therapeutic gymnastics took place in a virtual environment, in 60-minute sessions, twice a week, for 12 weeks. To compare the results of the quantitative variables, before and after the intervention, the nonparametric Wilcoxon test was used; the significance level adopted was P < 0.05. In the results before and after the intervention, no significant differences were found in the eight components of the SF-36. The responses of the volunteers in the qualitative assessment of participation pointed to favorable reports for health promotion. It has been concluded that this gymnastics in a virtual environment was effective for health promotion, although there was no change in the perception of quality of life.